Payroll Accounting Information System and its Impact on Internal Control of Manpower and Transmigration Office in Central Lombok Regency - Nur'aida; Sasanti, Elin Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the roles of accounting information systems is for internal control procedures. Internal control is the process of controlling and motivating employees by management to achieve goals. This study aims to determine the implementation of the payroll accounting information system and its impact on internal control of Manpower and Transmigration Office in Central Lombok Regency. The type of research used is qualitative research through field research. Data is obtained through observation, interviews, and documentation. The results showed that the payroll cycle was implemented using Regional Government Information System (SIPD). The results also showed that the payroll accounting information system has been in accordance with the provisions. However, the internal control system of the payroll cycle was still not good. Therefore, it can be said that internal control was still not good in general.